Geologia da Folha Rio Branco (SB-22-Y-V-VI), Província Carajás: mapeamento e integração de dados geológicos - FAVACHO, Gabriel Guimarães (2021)
The Carajás Province represents the largest preserved Archean nucleus of the Amazonian Craton. The Folha Rio Branco area (SB-22-Y-B-VI) is inserted in the northwestern portion of the Province, at the tectonic limit between the Rio Maria Domain and Carajás, where different types of granitoids and metamorphic rocks from low to high grade. This study deals with geological mapping on a semi-detailed scale of this area, which through aerogeophysical images (gamma spectrometry, magnetometry) has the purpose of discriminating and individualizing new geological units, which according to previous studies (regional scale) belonged to the Rio Maria Suite and to the Xingu Complex. Thus, eight radiometric anomalies were differentiated based on the concentration of radioactive elements (238U, 40K, 232Th) and it was noted the anomalies in the far north were most affected by magnetic lineaments, resulting in elongated/sigmoidal bodies. These aero geophysical data are reflected in two tectonic domains for Folha Rio Branco: Directional and Imbricado. The first is present in the central portion to the south of studied area, is composed of (i) metavolcanosedimentary rocks of the Tucumã Group and granitoids: (ii) trondhjemito, (iii) sanukitoide suite, (iv) monzogranitic-granodioritic association, (v) mafic/ultramafic rocks of the Suite Intrusiva Cateté and (vi) charnockites and associated rocks. The structural framework of this domain is formed by shear zones of NW-SE direction with moderate to high dip for NE and rarely for SW. The second domain (Imbricate) occurs from the central portion to the far north, it is composed of metamorphic rocks from (i) Grupo Sapucaia and (ii) migmatized gneiss, sometimes granulitized and granitoids: (iii) bt-tonalite, (iv) bt-leucogranodiorite, (v) mylonitized monzogranite, (vi) bt-leucogranite, (vii) bt-granite and (viii) mafic/ultramafic rocks from the Suite Intrusive Cateté. The structural framework of this domain is composed of astomosed shear zones that form an imbricated pattern of main direction E-W and present a moderate to high dip to N, which impose the geological units a geometry of the same direction. Three levels of formation were necessary for this segment of crust: low, medium and high milonitic grade, which together form a heterogeneous deformation. The older rocks have a scale of batholiths that reach great depths of the upper crust in section view, while the younger rocks occur intruded in the older ones, forming stocks, which when seen in section do not reach deep levels, except mafic/ultramafic rocks that the mantle level reaches. Occasionally, these rocks are mineralized by tin, gold, iron and are mined in mines such as Onça-Puma, Pedreira Milanos, Minera Sul. The evolutionary history of this crust segment seems to indicate a very complex evolution. The formation of the greenstones belts would be related to a metamorphism of oceanic plateaus generated under transpression regime. It was admitted to other areas of the Carajás Province, the formation of the Ourilândia and Tucumã areas would also have occurred initially in two stages in mesoarchean. Between 3.05 to 2.92 Ga, there would be the formation of trondhjemitic rocks, of TTG affinity that can be explained by either horizontal or vertical tectonics; between 2.87 to 2.86 Ga thermal events fuse the metasomatized mantle, which generates sanukitoid magmas and hybrid granites, which when lodged at the base of the crust and serve as a heat source for the melting of the overlying rocks to generate high-K granites.